ChemInform Abstract: Lateral Extension Induces Columnar Mesomorphism in Crucifix Shaped Quinoxalinophenanthrophenazines. Issue 21 (May 2015) - El‐Ballouli, Ala'a O.; Kayal, Himadri; Shuai, Chen; Zeidan, Tarek A.; Raad, Farah S.; Leng, Siwei; Wex, Brigitte; Cheng, Stephen Z. D.; Eichhorn, S. Holger; Kaafarani, Bilal R.
Abstract The reaction of 2, 7‐disubstituted tetraketopyrenes with dichlorophenylenediamine and subsequent substitution with long‐chain linear or multi‐branched thiols provides the title compounds.